Ionic cross-linking as a strategy tomodulate the properties of oral mucoadhesive microparticles based on polysaccharide blends - Boni, Fernanda Isadora [UNESP]; Cury, Beatriz S. F. [UNESP]; Ferreira, Natália Noronha [UNESP]; Gremião, Maria Palmira Daflon [UNESP] (MDPI, 2021)
Polymer blends of gellan gum (GG)/retrograded starch(RS) and GG/pectin (P) were cross-linked with calcium, aluminum, or both to prepare mucoadhesive microparticles as oral carriers of drugs or nano systems. Cross-linking with different cations promoted different effects on each blend, which can potentially be explored as novel strategies for modulating physical-chemical and mucoadhesive properties of microparticles. Particles exhibited spherical shapes, diameters from 888 to 1764 µm, and span index values lower than 0.5. Blends of GG: P cross-linked with aluminum resulted in smaller particles than those obtained by calcium cross-linking. GG: RS particles exhibited larger sizes, but cross-linking this blend with calcium promoted diameter reduction. The uptake rates of acid medium were lower than phosphate buffer (pH 6.8), especially GG: RS based particles cross-linked with calcium. On the other hand, particles based on GG: P cross-linked with calcium absorbed the highest volume of acid medium. The percentage of systems erosion was higher in acid medium, but apparently occurred in the outermost layer of the particle. In pH 6.8, erosion was lower, but caused expressive swelling of the matrixes. Calcium cross-linking of GG: RS promoted a significantly reduction on enzymatic degradation at both pH 1.2 and 6.8, which is a promising feature that can provide drug protection against premature degradation in the stomach. In contrast, GG: P microparticles cross-linked with calcium suffered high degradation at both pH values, an advantageous feature for quickly releasing drugs at different sites of the gastrointestinal tract. The high mucoadhesive ability of the microparticles was evidenced at both pH values, and the Freundlich parameters indicated stronger particle-mucin interactions at pH 6.8.
Keywords: Enzymatic degradation; Erosion; Gellan gum; Liquid uptake; Mucoadhesion; Pectin; Retrograded starch